The linkage between globalisation and financial inclusion: Do inequality and institutions matter? - Cahyadin, Malik (Economic Journal of Emerging Markets, 2020)
This paper examines the effect of the globalization threshold on financial inclusion in 40 selected countries during 2000-2018. A principal component analysis (PCA) and a static panel threshold (SPT) are utilized. There are three dimensions and one aggregation of financial inclusion indicators assessed by PCA, while the globalization threshold is estimated under static panel threshold regression. Findings/Originality: The findings exhibit six countries with strong financial inclusion and eight countries with weak financial inclusion during study periods. Furthermore, the threshold effect of globalization has a significant impact on the financial inclusion index. The robustness checking employs panel cointegration test exhibits that inequality and some institutions indicators have a significant impact on financial inclusion both in the short-run and long-run. The policy implication suggests that governments should increase the financial inclusion index level during the globalization period, decrease inequality, and improve institutions’ quality.